Climate-driven past and present interspecies gene flow may have contributed to shape microscale adaptation capacity in Tillandsia lomas in hyperarid south American desert systems - Stein, Ron Eric; Luque-Fernández, César R.; Kiefer, Christiane; Möbus, Johanna; Pauca-Tanco, G. Anthony; Jabbusch, Sarina; Harpke, Dörte; Bechteler, Julia; Quandt, Dietmar; Villasante, Francisco; Koch, Marcus (Global and planetary change, 2023)
Epiarenic (sand-growing) Tillandsia vegetation in the hyperarid and arid region of the Chilean-Peruvian Atacama Desert represents an extreme case of adaptation in plant species-poor ecosystems. The involved species exist at the limit of terrestrial life and form mono/oligo-specific and very characteristic structures within the landscape. Covering thousands of square kilometers they represent the major carbon sink in the hyperarid Atacama core. The various Tillandsia species and respective vegetation may have evolved and adapted independently to this extreme environment. The most abundant vicariant diploid species are T. landbeckii in Chile and T. purpurea in Peru. Spatio-temporally varying distribution range overlaps may have caused potentially adaptive gene flow between different species leading to present day gene pools. Using species distribution modelling we explored the idea that from Last Glacial Maximum (LGM) onwards both species shifted their distribution ranges, which resulted in the formation of varying suture zones from Peru towards northern Chile. We further explored genetic data from a Tillandsia loma vegetation in Southern Peru with three sympatrically growing species exemplifying inter-species gene flow crossing even ploidy levels. This mechanism highlights a strategy to evolve and adapt more rapidly to environmental changes in extreme arid and hyperarid habitats and provides an opportunity for Tillandsia populations to efficiently conserve new genotypes via subsequent clonal propagation.